31.9k views
4 votes
If f(x) = x-6 and g(x)= 1/2x (x+3), find g(x) * f(x)

1 Answer

0 votes

Answer:

Final answer is
g\left(x\right)\cdot f\left(x\right)=(\left(x-6\right))/(2x\left(x+3\right)).

Explanation:

given functions are
f(x)=x-6 and
g\left(x\right)=(1)/(2x\left(x+3\right)).

Now we need to find about what is the value of
g\left(x\right)*f\left(x\right).


g\left(x\right)*f\left(x\right) simply means we need to multiply the value of
f(x)=x-6 and
g\left(x\right)=(1)/(2x\left(x+3\right)).


g\left(x\right)\cdot f\left(x\right)=(1)/(2x\left(x+3\right))\cdot\left(x-6\right)


g\left(x\right)\cdot f\left(x\right)=(\left(x-6\right))/(2x\left(x+3\right))

Hence final answer is
g\left(x\right)\cdot f\left(x\right)=(\left(x-6\right))/(2x\left(x+3\right)).

User Keziah
by
5.0k points